Experiential Learning in Ghana: Decentering the White Voice - Chapdelaine, Robin; Toomer, Megan (Radical Teacher, 2021)
White supremacy served as the foundation of the transatlantic slave trade and the subsequent practice of chattel slavery in the United States.[i] As such, it is not an exaggeration to say that US history is rooted in the oppression of non-white populations who have experienced and continue to experience various forms of physical and emotional harm. It is in this context that we examine how undergraduate students from XXX University, a predominantly white liberal arts institution, experienced the summer 2019 study abroad ‘Maymester’ excursion to Ghana where the transatlantic slave trade was the main focus of one of the courses, Precolonial African history.[ii] We argue that an interracial dialogue on the terror of whiteness on Black bodies and in Black spaces, which is steeped in historical context, develops when white student voices do not predominate classroom discussions. By centering the co-author’s account of the program, we show that when decentering the white voice, which is generally that of the dominant student population, white students can achieve a reconsideration of their understanding of self, others, and of African and global histories. This article also stresses the importance prioritizing cultural competence as a student goal in light of some of the preconceived notions they held about Ghana and Africa, and finally, we argue that universities have a moral responsibility to introduce Anti-racist pedagogy into the classrooms as a measure to fight white supremacist ideology. [i] Gary Dorrien, “Achieving the Black Social Gospel, “ Breaking White Supremacy: Martin Luther King Jr. and the Black Social Gospe (New Haven, CY: Yale University Press, 2018), 1. [ii] Split into two courses, the four-week study program spanned two weeks each.